2005
DOI: 10.1681/asn.2004050425
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reactive Oxygen Species in TGF-β1-Induced Mitogen-Activated Protein Kinase Activation and Epithelial-Mesenchymal Transition in Renal Tubular Epithelial Cells

Abstract: Epithelial-mesenchymal transition (EMT) plays an important role in renal tubulointerstitial fibrosis and TGF-␤1 is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
389
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(427 citation statements)
references
References 38 publications
32
389
0
1
Order By: Relevance
“…The mechanism by which TGF-β induces DDR is unclear. However, TGF-β is known to induce reactive oxygen species that can promote EMT, oxidative damage to DNA, and genomic instability in mouse mammary epithelial cells (25,26). Our data demonstrate that in HOXB9-expressing cells the induction of γ-H2AX and 53BP1 foci before irradiation and accelerated DDR after ionizing radiation are mediated in part through the HOXB9-TGF-β-ATM axis.…”
Section: Discussionmentioning
confidence: 69%
“…The mechanism by which TGF-β induces DDR is unclear. However, TGF-β is known to induce reactive oxygen species that can promote EMT, oxidative damage to DNA, and genomic instability in mouse mammary epithelial cells (25,26). Our data demonstrate that in HOXB9-expressing cells the induction of γ-H2AX and 53BP1 foci before irradiation and accelerated DDR after ionizing radiation are mediated in part through the HOXB9-TGF-β-ATM axis.…”
Section: Discussionmentioning
confidence: 69%
“…TGF-b can induce an ROS- PNC1 regulates mitochondrial function and EMT C Favre et al dependent EMT in epithelial cells (Rhyu et al, 2005). As shown in Figure 7c, control MCF-7 cells lost E-cadherin expression when stimulated with TGF-b, whereas cells overexpressing PNC1 retained E-cadherin levels.…”
Section: Ros As Shown Inmentioning
confidence: 84%
“…31,32 In contrast, it was recently reported that ROS production inhibits the EMT in prostate cancer cells. 58 Because the EndMT is also observed in tumor cells, it would be interesting to explore whether oxidative stress inhibits the EndMT in cancer cells.…”
Section: Discussionmentioning
confidence: 95%
“…Human epidermal keratinocytes exposed to H 2 O 2 showed protein expression that was consistent with the EMT, 31 and similar results were founded in renal tubular epithelial cells. 32 In the same way, chromium-induced EMT is dependent on intracellular ROS in lung epithelial cells. 33 A specialized EMT process is the endothelial-to-mesenchymal transition (EndMT).…”
mentioning
confidence: 98%